2020
DOI: 10.1038/s41598-020-78375-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diaphragmatic excursion and lung compliance during gynaecologic surgery: open laparotomy versus laparoscopy—a prospective observational study

Abstract: This study compared the effects of open versus laparoscopic radical hysterectomy on intraoperative diaphragmatic excursion and lung compliance. We enrolled 20 women per group; Group O’s members underwent open radical hysterectomy, while Group L’s members underwent laparoscopic radical hysterectomy. Diaphragmatic excursion was measured by assessing tidal ventilation using M-mode ultrasonography before intubation (T0), after intubation with mechanical ventilation (T1), 90 min after incision (T2), and at the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In recent years, due to the advantages of a small incision and enhanced recovery after surgery, laparoscopic surgery has gradually become the primary abdominal surgery [ 1 ]. However, the establishment of pneumoperitoneum leads to the displacement of the diaphragm to the head, reduces the functional residual capacity (FRC), and promotes the formation of atelectasis, thus leading to impaired respiratory mechanics and gas exchange [ 2 , 3 ]. More importantly, pulmonary atelectasis underlies the pathophysiology of PPCs, the development of which may prolong hospital stays and increase mortality in surgical patients [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, due to the advantages of a small incision and enhanced recovery after surgery, laparoscopic surgery has gradually become the primary abdominal surgery [ 1 ]. However, the establishment of pneumoperitoneum leads to the displacement of the diaphragm to the head, reduces the functional residual capacity (FRC), and promotes the formation of atelectasis, thus leading to impaired respiratory mechanics and gas exchange [ 2 , 3 ]. More importantly, pulmonary atelectasis underlies the pathophysiology of PPCs, the development of which may prolong hospital stays and increase mortality in surgical patients [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Trendelenburg position and pneumoperitoneum force the diaphragm towards the cranial side, leading to a decrease in lung volume and an increase in airway pressure. It has been suggested that the decrease in lung volume during surgery and the anatomical characteristics of the diaphragm itself are possible reasons for postoperative diaphragm movement impairment, although this view remains contentious [ 5 ]. Factors contributing to diaphragmatic dysfunction are multifaceted.…”
Section: Discussionmentioning
confidence: 99%
“…With the patient in the Trendelenburg position, gravity forces to keep the intestines away from the pelvis and abdominal cavity, which improves visualization and accessibility by creating more space in the surgical area and reduces the risk of injury by avoiding unexpected movement of organs and tissues. Although the Trendelenburg position provides numerous benefits during robot-assisted surgery, it is not without potential dangers, with the lungs and diaphragm bearing the brunt [ 4 , 5 ]. On one hand, the displacement of abdominal organs towards the chest leads to decreased lung volumes and compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Among these patients, LUS most commonly manifests as B line signs in the gravity-dependent lung area and irregularities and ruptures of the pleura. The above-mentioned LUS signs appear not only due to the effect of gravity, which causes the liquid to distribute to the lowered part, resulting in changes in gasliquid distribution, but also considered to be related to the changes in the respiratory system of patients after induction of general anesthesia, which leads to lung in ation defects [21] .In addition, during laparoscopic surgery, the increase in intra-abdominal pressure pushes the diaphragm muscle cephalad, causing changes in lung volume that exacerbate the formation of atelectasis in the gravity-dependent area of the lung [25] . Monastesse et al [9] pointed out that although the pulmonary ventilation defect caused by pneumoperitoneum was not as severe as that induced by general anesthesia, a signi cant increase in LUSS after pneumoperitoneum could be observed.…”
Section: Discussionmentioning
confidence: 99%